2015
DOI: 10.1002/btpr.2141
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone-loaded biopolymeric nanoparticles promote gingival fibroblasts differentiation

Abstract: Polymer-based nanoparticles (NPs) can be efficiently used for the delivery of bioactive molecules for both in vitro and in vivo applications affording high drug loading and controlled release profiles. Within this framework polylactic-co-glycolic acid (PLGA) NPs with a diameter of 290 ± 41 nm have been fabricated and loaded with dexamethasone (DXM) using a patented procedure. The aim of the project was to setup a controlled delivery system to promote the in vitro differentiation of Human Gingival Fibroblasts (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…To visualize the cellular uptake of NPs, the fluorescent 6-coumarin probe was used. In a previous study [61], we have already demonstrated that 6-coumarin-loaded CS-PLGA NPs were internalized inside HGFs and uptake saturation was reached after 2 h of incubation [61]. In this study we have confirmed this result and we have also showed that-as expected-PE/CA-PJ15 cells are able to internalize 6-coumarin-loaded CS-PLGA NPs with kinetics similar to HGFs (figure 8).…”
Section: Ga-nps and Ga-fbs Characterizationsupporting
confidence: 86%
See 2 more Smart Citations
“…To visualize the cellular uptake of NPs, the fluorescent 6-coumarin probe was used. In a previous study [61], we have already demonstrated that 6-coumarin-loaded CS-PLGA NPs were internalized inside HGFs and uptake saturation was reached after 2 h of incubation [61]. In this study we have confirmed this result and we have also showed that-as expected-PE/CA-PJ15 cells are able to internalize 6-coumarin-loaded CS-PLGA NPs with kinetics similar to HGFs (figure 8).…”
Section: Ga-nps and Ga-fbs Characterizationsupporting
confidence: 86%
“…In order to evaluate the NPS cell uptake, fluorescent NPs were prepared by dissolving PLGA and 6-coumarin in acetone and proceeding as reported elsewhere [61].…”
Section: Nps Cell Uptake: Internalization Of 6-coumarinmentioning
confidence: 99%
See 1 more Smart Citation
“…Gingival fibroblasts (GFs) have gained use in biomaterial research due to easiness and high availability of gingival biopsies, low morbidity of the donor sites, the high proliferative potential and cell yielding, and their inclusion of multipotent mesenchymal stem cells (Alfonso García et al, 2020;Fournier et al, 2010Fournier et al, , 2013. The regenerative potential of GFs was built on the wellknown fast and scarless healing of oral mucosa, and it is proven in multiple experimental studies: they express bone-associated factors (Ivanovski et al, 2001), they convey stemness and multipotency (Fournier et al, 2010(Fournier et al, , 2013 and can acquire osteogenic/mineralizing phenotype (Bermúdez et al, 2015;Chronopoulou et al, 2015;Mostafa et al, 2011) and their scretome promotes wound healing (Ahangar et al, 2020) and the regeneration of pulp (Vu et al, 2022) and periodontal (Qiu et al, 2020) tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous experiments obtained chondrogenesis of human mesenchymal stem cells by exposing cells to PLGA NPs that incorporated chondrogenesis-related proteins, transcription factors, or genes. Of interest also is the fact that PLGA nanocarriers have been developed to deliver active molecules for other possible dental-related applications: transport of dexamethasone for gingival fibroblasts differentiation [149] or controlled release of amphotericin B for fighting against fungal infections [150]. Novel skin cancer treatments could include PLGA NPs [163] transporting small molecules, RNA or genes in order to target the p53 inactivation or the epidermal growth factor receptor over-expression in skin squamous carcinoma tumors [164].…”
Section: Synthetic Organic Nano-delivery Systemsmentioning
confidence: 99%